Central Composite Design for the Development and Evaluation of Liquisolid Compacts of Glyburide - Patil, Archana; Kauthankar, Bhakti; Kavatagimath, Satish; Masareddy, Rajashree; Dandagi, Panchaxari (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Glyburide is an oral antidiabetic agent with a shorter half-life and is practically insoluble in water. As a result, there is a need to enhance the drug solubility with a aim to improve drug absorption via the oral route. The goal of this study was to formulate, optimize and evaluate the liquisolid tablets of Glyburide using a suitable liquid vehicle in order to enhance the solubility, and bioavailability of the Glyburide. Materials and Methods: The liquisolid compacts of Glyburide were prepared by direct compression method using approved excipients. Using central composite design, the amount of Transcutol HP and carrier: coating ratio to be added in the formulations of Glyburide liquisolid compact has been theoretically generated by the software. The liquisolid tablets were evaluated for thickness and diameter, hardness, weight variation, friability, content uniformity, disintegration time, in-vitro dissolution study and compared with marketed product. Results: The prepared liquisolid system exhibited good flow-properties. The allpost compression parameters were well within the specified limits. The release profile of optimal formulation revealed higher drug release compared to marketed formulation. Increases in the concentration of liquid vehicle and carrier: coating material ratio resulted in an increase in the dissolution rate. Conclusion: The liquisolid compact method was discovered to be a potential method to enhance the dissolution profile, thereby enhancing the solubility of the Glyburide.
Keywords: Liquisolid technique; Glyburide; Central composite design; Aerosil200; Transcutol HP; Avicel PH-102